1992
DOI: 10.1128/aac.36.12.2589
|View full text |Cite
|
Sign up to set email alerts
|

Induction of topoisomerase II-mediated DNA cleavage by the plant naphthoquinones plumbagin and shikonin

Abstract: Plumbagin and shikonin, plant metabolites which have naphthoquinone structures, induced mammalian topoisomerase II-mediated DNA cleavage in vitro. Treatment of a reaction mixture containing these naphthoquinones and topoisomerase II at an elevated temperature (65°C) resulted in a great reduction in DNA cleavage, suggesting that the mechanism of the topoisomerase II-mediated DNA cleavage induced by these naphthoquinones is through formation of a cleavable complex, as seen with antitumor agents such as 4'-(9-acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 36 publications
2
81
0
4
Order By: Relevance
“…Most of these quinoids belong to DNA-intercalating agents (16,17). For instance, Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), derived from Plumbagineae and Droseraceae families, can induce mammalian topoisomerase II-mediated DNA cleavage in vitro (18). Therefore, they are effective anticancer agents against murine fibrosarcoma, P388 lymphocytic leukemia, and A549 non-small cell lung cancer cells (19 -21).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these quinoids belong to DNA-intercalating agents (16,17). For instance, Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), derived from Plumbagineae and Droseraceae families, can induce mammalian topoisomerase II-mediated DNA cleavage in vitro (18). Therefore, they are effective anticancer agents against murine fibrosarcoma, P388 lymphocytic leukemia, and A549 non-small cell lung cancer cells (19 -21).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effects of these quinones are mainly due to the inhibition of DNA topoisomerase -II. 1,2 Naphthoquinones are widely distributed in plants, fungi and some animals, and most of these are found to exhibit an interesting range of pharmacological properties. 1,4-Naphthoquinone is an important example of quinone family and is used as a raw material in pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 1,4-Naphthoquinone derivatives were proved to be human DNA topoisomerase I and II inhibitors. 2 The presence of two carbonyl groups in naphthoquinones that have the ability to accept one or two electrons to form the corresponding radical anion or di-anion species and their acid-base properties is responsible for the various biological activities. 17,18 In another study, it was found that the presence of hydroxy groups at 5 and 8 positions, which facilitate the tautomerism in the structure of 1,4-naphthoquinone, reduced the electrophilicity of the naphthoquinone ring.…”
Section: Introductionmentioning
confidence: 99%
“…4 Shikonin is one of the active ingredients isolated from the roots of the traditional oriental medicinal herb Lithospermium erythrorhizon. 5 Many studies showed that shikonin exerted antitumor effects by inhibiting cancer cell growth, 6 inducing apoptosis 7 and inhibiting DNA topoisomerase I/II activity, [8][9][10] antitelomerase activity 11 and antiangiogenesis. 12 Because of its poor solubility and toxicity, shikonin have little potential to be an anticancer drug.…”
mentioning
confidence: 99%